2004
DOI: 10.2135/cropsci2004.1966
|View full text |Cite
|
Sign up to set email alerts
|

Moving beyond the Winter Hardiness Plateau in U.S. Oat Germplasm

Abstract: ABSTRACTniques involved evaluation of individual lateral crown meristem tissue from which root and shoot regrowth is Progress has been slow in the development of winter-hardy oat regenerated (Marshall, 1965). Marshall and Kolb (1982) (Avena sativa L.) cultivars. No cultivar released in the last 40 yr has better freezing tolerance than the cultivar Norline, which was released increased the winter hardiness of two heterogeneous

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 12 publications
0
7
1
Order By: Relevance
“…Livingston and Elwinger (1995) found that Wintok and Norline had similar mean winter fi eld survival but often performed diff erently in some environments. Germplasm lines with increased crown freezing tolerance were developed from a cross between Norline and Wintok (Livingston et al, 2004) and some of these were significantly more winter hardy than either Norline or Wintok (Livingston, Uniform Oat Winter Hardiness Nursery, unpublished data, 2004-2006. These results from crosses of Norline and Wintok support the hypo thesis that Wintok has a gene for winter fi eld survival associated with T7C-17 not present in Norline, while Norline has genes not present in Wintok for crown freezing tolerance that are not associated with T7C-17.…”
Section: Translocation Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Livingston and Elwinger (1995) found that Wintok and Norline had similar mean winter fi eld survival but often performed diff erently in some environments. Germplasm lines with increased crown freezing tolerance were developed from a cross between Norline and Wintok (Livingston et al, 2004) and some of these were significantly more winter hardy than either Norline or Wintok (Livingston, Uniform Oat Winter Hardiness Nursery, unpublished data, 2004-2006. These results from crosses of Norline and Wintok support the hypo thesis that Wintok has a gene for winter fi eld survival associated with T7C-17 not present in Norline, while Norline has genes not present in Wintok for crown freezing tolerance that are not associated with T7C-17.…”
Section: Translocation Effectsmentioning
confidence: 99%
“…Norline is a winter‐hardy cultivar developed by the Indiana USDA‐ARS oat breeding program and released in 1960 (Patterson and Schafer, 1978). It is winter hardy (Livingston and Elwinger, 1995; Livingston et al, 2004) and contains T7C‐17 (Jellen and Beard, 2000). Norline and Wintok are the long‐term winter‐hardy checks in the Uniform Oat Winter Hardiness Nursery and have similar mean winter hardiness, but often differ for winter field survival in some environments (Livingston and Elwinger, 1995).…”
mentioning
confidence: 99%
“…A stagnation was recorded in oat winter hardiness in the second half of the last century until a progress was reported in North Caroli na, USA, first as a result of crossing the winterhardy cultivars ' Wintok' and 'Norline' (Liv ingston, Elwinger, 1995;Livingston et al, 2004), and later after application of the wild species Avena macrostachya Bal. ex Coss et Dur.…”
Section: Introductionmentioning
confidence: 99%
“…A stagnation was recorded in oat winterhardiness in the second half of the last century until a progress was reported in North Carolina, USA, first as a result of crossing the winterhardy cultivars 'Wintok' and 'Norline' (Livingston, Elwinger, 1995;Livingston et al, 2004), and later after application of the wild species Avena macrostachya Bal. ex Coss et Dur.…”
Section: Introductionmentioning
confidence: 99%